2021
DOI: 10.3389/fmolb.2021.600881
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Nucleosomes as Potential Markers to Monitor COVID-19 Disease Progression

Abstract: The severity of coronavirus disease 2019 (COVID-19) varies significantly with cases spanning from asymptomatic to lethal with a subset of individuals developing Severe Acute Respiratory Syndrome (SARS) and death from respiratory failure. To determine whether global nucleosome and citrullinated nucleosome levels were elevated in COVID-19 patients, we tested two independent cohorts of COVID-19 positive patients with quantitative nucleosome immunoassays and found that nucleosomes were highly elevated in plasma of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 40 publications
4
27
0
Order By: Relevance
“…This is consistent with prior reports of elevated NETs in COVID-19, as evidenced by increased cell-free DNA, myeloperoxidase-DNA complexes, and citrullinated-Histone H3 [21][22][23]. Similar observations were recently made in two independent cohorts of COVID-19 positive patients with a quantitative nucleosome immunoassay that measured cell-free H3.1 nucleosomes [24]. These investigators demonstrated that nucleosomes were highly elevated in plasma of COVID-19 patients with a severe course of the disease relative to healthy controls and that both the histone 3.1 variant and citrullinated nucleosomes increase with disease severity.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with prior reports of elevated NETs in COVID-19, as evidenced by increased cell-free DNA, myeloperoxidase-DNA complexes, and citrullinated-Histone H3 [21][22][23]. Similar observations were recently made in two independent cohorts of COVID-19 positive patients with a quantitative nucleosome immunoassay that measured cell-free H3.1 nucleosomes [24]. These investigators demonstrated that nucleosomes were highly elevated in plasma of COVID-19 patients with a severe course of the disease relative to healthy controls and that both the histone 3.1 variant and citrullinated nucleosomes increase with disease severity.…”
Section: Discussionsupporting
confidence: 92%
“…Increased serum levels of neutrophil-derived MPO-DNA and citrullinated histone H3, both NET degradation products, closely parallel lung distress and predict COVID-19 severity [ 52 ]. Furthermore, circulating nucleosomes were identified as potential markers to monitor COVID-19 disease progression [ 119 ]. Immature and low-density neutrophils predominate in severe COVID-19 [ 15 , 16 , 120 ].…”
Section: Nets’ Impact At the Organ Levelmentioning
confidence: 99%
“…Some isozymes of PAD, including PADI1 and PADI6, were elevated but to a less significant degree. Inspection of nucleosomes levels in SARS-CoV-2 infected patients [ 17 ] further corresponds with the elevations observed in DVT-induced mice. Patients diagnosed with COVID-19 were observed to have elevated levels of histone variant H3.1 and H3R8 compared to controls, more prominently among patients admitted into intensive care units (ICU) compared to non-ICU patients positive for COVID-19 [ 17 ].…”
Section: Netosis and Citrullinated Histones Potentiate Immunothrombosismentioning
confidence: 74%
“…Inspection of nucleosomes levels in SARS-CoV-2 infected patients [ 17 ] further corresponds with the elevations observed in DVT-induced mice. Patients diagnosed with COVID-19 were observed to have elevated levels of histone variant H3.1 and H3R8 compared to controls, more prominently among patients admitted into intensive care units (ICU) compared to non-ICU patients positive for COVID-19 [ 17 ]. The increased NETs and associated turnover products described in prior studies are evidenced to assist in occlusion of vasculature, notably pulmonary vessels [ 5 ].…”
Section: Netosis and Citrullinated Histones Potentiate Immunothrombosismentioning
confidence: 74%